Pengaruh Pendidikan kewirausahaan, pengelolaan keuangan dan minat terhadap keberhasilan PKL ( pedagang kaki lima ) di Malang - Mientarti W, Sri Umi (Fakultas Ekonomi Universitas Wisnuwardhana, 2013)
The purpose of this study was to determine the effect of entrepreneurship education, financial management, and interest in the success of Street Vendors tried in the city of Malang. The population in this study were all street vendors in the city of Malang, both are available on the spot, as well as those walking around hawking wares, which numbered 226 people. The research sample was taken using the formula Solvin as many as 33 people taken at random proportional. Retrieval of data using questionnaires and interviews. Data analysis was performed using multiple regression analysis with the dependent variable of success trying, while the independent variable is entrepreneurship education, financial management and interest in trying. The results showed that the variables of the street vendors entrepreneurship education has a positive effect on the success siqnifikan street vendors in trying. Due to their knowledge of entrepreneurship will be able to do what should be done by the employer, such as the need to communicate with customers, in order to established a good relationship with the consumer, the consumer will ultimately become loyal customers. Knowledge of good financial management, will make the street vendors were able to develop their business well, because the street vendors will be able to calculate correctly, what is rightfully his, and how many obligations. Interests of street vendors trying to influence the success of the street vendors in developing their businesses.Keywords: entrepreneurship education, financial management, business interests and success of the business merchandisers.